QUANTITATIVE PHOSPHOPROTEOMIC ANALYSIS OF SIGNALING NETWORK DYNAMICS - White, Forest M. (2008)
Protein phosphorylation mediated cellular signaling is a highly regulated, dynamic process that controls many aspects of cellular biology. Over the past few years many methods have been developed to quantify temporal dynamics of protein phosphorylation, including mass spectrometry, which can be applied in both an unbiased, discovery mode and in a targeted mode to monitor specific phosphorylation sites. Other methods, such as kinase activity assays and antibody microarrays, have been applied to quantify central nodes in the signaling network, yielding intriguing biological insights. This review provides a concise overview of the latest advances in quantitative analysis of signaling dynamics including a brief commentary on the future of the field.